Dielectric relaxation and electrical conductivity of random oriented BiFeO3 thin films - Reis, S. P. [UNESP]; Araujo, E. B. [UNESP] (Taylor & Francis Ltd, 2019)
Complex impedance and electric modulus spectroscopies were used to investigate the dielectric relaxation and conductivity of random oriented BiFeO3 thin films. Thermally activated charge transport models yielded activation energies of eV, which is consistent with an electrical conduction dominated by oxygen vacancies. The non-Debye behavior of impedance and electric modulus relaxations were modeled by Cole-Cole functions. Results suggest a coexistence of components from both long-range and localized relaxation in the studied BiFeO3 films dominated by grain boundaries. The dielectric relaxation induced by electric field does not follow the Arrhenius formalism.
Keywords: Bismuth ferrite; thin films; dielectric relaxation